19 | | * In more than 1D, [[latex($\nabla \cdot \left [\frac{1}{2} \frac{\left (\nabla \phi : \nabla \phi \right )}{4 \pi G} + \bar{\rho} \phi I \right ]_i =\partial_j (\partial_j \phi \partial_i \phi) +\bar{\rho} \partial_i \phi$)]] |
| 19 | * In more than 1D we have |
| 20 | |
| 21 | |
| 22 | {{{ |
| 23 | #!latex |
| 24 | \begin{align*} |
| 25 | \partial_t p_i&=\rho \partial_i \phi \\ |
| 26 | & = \left (\frac{\partial_j(\partial_j \phi)}{4 \pi G}+\bar{\rho} \right ) \partial_i \phi \\ |
| 27 | & = \partial_j \left ( \partial_j \phi \partial_i \phi \right) - (\partial_j \phi) \partial_j (\partial_i \phi )+\partial_i (\bar{\rho}\phi) \\ |
| 28 | & = \partial_j \left ( \partial_j \phi \partial_i \phi \right) - (\partial_j \phi) \partial_i (\partial_j \phi )+\partial_i (\bar{\rho}\phi) \\ |
| 29 | & = \partial_j \left ( \partial_j \phi \partial_i \phi \right) - \frac{1}{2}\partial_i(\partial_j \phi \partial_j \phi)+\partial_i (\bar{\rho}\phi) \\ |
| 30 | & = \partial_j \left ( \partial_j \phi \partial_i \phi \right) - \partial_i \left (\frac{\partial_j \phi \partial_j}{2} \phi+\bar{\rho}\phi \right) \\ |
| 31 | & = \partial_j \left ( \partial_j \phi \partial_i \phi \right) - \partial_j \left ( \delta ^i_j\left(\frac{\partial_k \phi \partial_k \phi}{2}+\bar{\rho}\phi \right) \right) \\ |
| 32 | & = \partial_j T_{ij} \mbox{ where } T_{ij} = \left ( \partial_j \phi \partial_i \phi \right) - \delta ^i_j\left(\frac{\partial_k \phi \partial_k \phi}{2}+\bar{\rho}\phi \right) \\ |
| 33 | \end{align*} |
| 34 | }}} |
23 | | * Also athena stores combined kinetic/thermal/magnetic with gravitational... So [[latex($E_{Athena}=E_{Astrobear}+\rho\phi$)]]. This results in [[latex($\dot{E}_{Athena}=\dot{E}_{Astrobear}+\dot{\rho}\phi = \rho \nabla \phi \cdot \mathbf{v}+\phi \nabla \cdot (\rho \mathbf{v}) = \nabla \cdot (\rho \mathbf{v} \phi)$)]] so the energy source term for self gravity can be written as a total divergence. We need [[latex($\rho v \phi$)]] at cell edges, but [[latex($\rho v$)]] is available from the mass flux and [[latex($\phi$)]] can be averaged using adjacent cells. |
| 38 | * As as the energy is concerned... |
| 39 | Currently the energy added is [[latex($\Delta E_i = \frac{\Delta t}{2\Delta x} \left[(\rho v)_{i-1/2}\Delta x \left(-\frac{\phi_{i}-\phi_{i-1}}{\Delta x} \right) - (\rho v)_{i+1/2}\Delta x \left(+\frac{\phi_{i+1}-\phi_{i}}{\Delta x}\right )\right ]$)]] |
| 40 | |
| 41 | Which is equivalent to |
| 42 | |
| 43 | [[latex($-\Delta t \left [ \frac{ (\rho v \nabla \phi)_{i+1/2} + (\rho v \nabla \phi)_{i-1/2}}{2} \right ] $)]] |
| 44 | |
| 45 | |
| 46 | If we try to express the energy source term as a total flux we get |
| 47 | |
| 48 | [[latex($\dot{E_{kinetic}} = f_{grav} \cdot v = \rho \nabla \phi \cdot v = \rho v \cdot \nabla \phi = \nabla \cdot (\rho v \phi)-\phi \nabla \cdot {\rho v} = \nabla \cdot {\rho v \phi} - \phi \nabla \cdot {v \nabla^2\phi}$)]] |
| 49 | |
| 50 | The presence of the v will make it impossible to right this as a total flux. |
| 51 | |
| 52 | What if we store the potential in E? Then [[latex($\dot{E}= \nabla \cdot (\rho v \phi) - \rho \dot{\phi}$)]] |
| 53 | |
| 54 | We now have a flux as well as a source term. However, the integral of the source term would need to be zero. So our elliptic equation would have a constraint |
| 55 | |
| 56 | |
| 57 | [[latex($\nabla^2\phi=4 \pi G \rho$)]] |
| 58 | |
| 59 | [[latex($\int{\rho \dot{\phi}} = 0$)]] |
| 60 | |
| 61 | |
| 62 | |
| 63 | |
| 64 | |
| 65 | We can conserve total energy before and after the hydro step if we add source terms to the Energy [[latex($\dot{E}=f_{grav} \cdot \mathbf{v} = \rho \nabla \phi \cdot \mathbf{v} = \rho \mathbf{v} \cdot \nabla \phi = \nabla \cdot \left (\rho \mathbf{v} \phi \right) - \phi \nabla \cdot \left ( \rho \mathbf{v} \right ) = \nabla \cdot \left (\rho \mathbf{v} \phi \right) - \phi \dot{\rho}$)]] |
| 66 | |
| 67 | |
| 68 | Consider the difference in gravitational energy... |
| 69 | |
| 70 | [[latex($\dot{E_{grav}} = \dot{(\rho\phi)}=\dot{\rho}{\phi}+\rho\dot{\phi}= \nabla \cdot (\rho v) \phi + \rho \dot{\phi} = \nabla \cdot (\rho v \phi) - \rho v \cdot \nabla \phi + \rho \dot{\phi}$)]] |
| 71 | |
| 72 | As well as kinetic energy |
| 73 | |
| 74 | [[latex($\dot{E_{kinetic}} = f_{grav} \cdot v = \rho \nabla \phi \cdot v = \rho v \cdot \nabla \phi$)]] |
| 75 | |
| 76 | For the sum to be zero we need to have [[latex($\nabla \cdot (\rho v \phi) = \rho \dot{\phi}$)]] |
| 77 | |
| 78 | The first term [[latex($\dot{\rho}{\phi} = \nabla \cdot (\rho v) \phi = \nabla \cdot (\rho v \phi) - \rho v \cdot \nabla \phi$)]] so we could identify a gravitational energy flux term [[latex($=\rho v \phi$)]] |
| 79 | |
| 80 | |
| 81 | |